Operational Groups of the NKGB and a Reconstruction of the Soviet Security Apparatus in Axis Occupied Ukraine, 1943–44 - Melnyk, Oleksandr (East/West)

(untitled) (Canadian Institute of Ukrainian Studies University of Alberta, 2023)
This article elucidates the reconstruction of the Soviet security apparatus during World War II in what today is western Ukraine. In late 1943 to early 1944, six operational groups of the People’s Commissariat of State Security of the Ukrainian Soviet Socialist Republic headed to the Axis occupied territories with orders to re-establish contacts with Soviet secret agents and create a support infrastructure for the deployment of other operational groups, special purposes units, and individual agents, as well as to infiltrate organizations of Polish and Ukrainian nationalists. The essay examines Soviet special operations within the context of state efforts to project power into the Axis occupied territories. It sheds light on the objectives of Soviet security agencies and on the activities of individual units in the field.